Participatory land-use approach for integrating climate change adaptation and mitigation into basin-scale local planning. (November 2017) - Endo, Isao; Magcale-Macandog, Damasa B.; Kojima, Satoshi; Johnson, Brian A.; Bragais, Milben A.; Macandog, Paula Beatrice M.; Scheyvens, Henry
Abstract: Literature suggests a significant potential for synergies among climate change adaptation and mitigation (CCA&M) policies, especially in urban areas. However, the understanding of how best to integrate CCA&M is limited despite the fact that there is an increasing interest, particularly in Southeast Asian countries, in achieving the integration. One such synergistic approach is to improve land-use with climate change consideration. This study aims to test this idea, conducting a pilot project with four local governments in the Silang-Sta. Rosa subwatershed of the Philippines, focusing on flood prevention that has strong spatial implications. The application of participatory watershed land-use management (PWLM), a systematic process with practical tools (e.g. scenario simulation, risk assessment), indicated that planned land-use conversion and projected climate change are likely to increase the intensity of flooding in the study area. Zoning enhancement is essential as a countermeasure. As one example, runoff neutral development measures would reduce the number of flood-affected people from approximately 226, 410 to 183, 349 in the future (year 2025), while preserving existing vegetation would prevent up to 528, 142 tons of CO2 emissions. Illustrating the PWLM approach, this paper demonstrates the concrete use of scientific knowledge (i.e. flood hazard) for local planners to design climate change action.